The Role of Social Support on the Mental Health of Royal Malaysia Police (PDRM) Officers/ Peranan Sokongan Sosial Terhadap Tahap Kesihatan Mental Dalam Kalangan Polis Diraja Malaysia (PDRM) (Sains Humanika, 2025)
This study focuses on examining the role of social support on the level of mental health among police officers in Malaysia. Social support in this study refers to support from supervisors and peers while mental health involves elements of depression, anxiety and stress. This study will identify the level of social support and the level of mental health among police personnel. This study also examines the relationship and influence of social support (supervisors, co-workers) on mental health (depression, anxiety and depression). A total of 615 police officers members were involved as a study sample. Depression, Anxiety and Stress Questionnaire (Depression, Anxiety and Stress Scale -DASS-21) was used to measure the level of mental health while the Social Support Scale was used to measure social support from supervisors and co-workers. The data obtained was analyzed using the Statistical Package of Social Sciences (SPSS) software version 29. The analysis performed included frequency analysis, percentage, pearson correlation and regression. The findings of the study show that the level of social support (support from supervisors and co-worker) among PDRM members is moderate while the level of mental health (depression, anxiety and stress) among PDRM members is normal. In addition, this study revealed that social support from supervisor and co-worker have significantly negative relationship mental health among PDRM officers in Malaysia. The findings of the study also show that support from supervisors and co-worker play a significant role in influencing the level of mental health. In conclusion, the results of this study will be able to be used as a reference and guide to help in improving the level of mental health by encourage social support among PDRM officers in Malaysia.
Keywords: social support, mental health, police officers